Phone virtual environment for RC assistive robot - Zargoun, Ahmed Muftah Ali (2014)
Robotic systems nowadays are all around us and interact in many aspects such as homeowners use robotic vacuums in their homes. However, a push needed to make these systems more and more interactive with humans. The complexity of the robot controller might be one of the boundaries between the robot interactions with human. An assistive robot with an Android phone controller needed since smart phones nowadays are used almost by everyone. This assistive robot controller does not require much effort from the user, just needs moving a finger to control them. This project uses SolidWorks and Processing in the software development phase. The IOIO board has been applied as a main controller to run the system as an embedded system, and integrate the android application with the assistive robot. The communication has been established using the standard 0 dBm radio Bluetooth with range of 10 meters radius. The joint have a good desired tracking with less than 1% error. Finally the aim of this project, which is a user friendly smart phone application to monitor and control the assistive robot has been developed.